Critical Analysis of the Integration of Health it in Epidemiological Research - Qadi, Hussain Ahmed Mohammed; Sakk, Adel Ahmed; Jaafari, Ibrahim Mohammed Ahmed; Alkhayrat, Mansour Alhassan Ahmad; Mudarbish, Mutaen Ali Yahya; Mujarribi, Hisham Abdullah Hussain; Almakrami, Ibrahim Hussain Ahmad; Al Omar, Ali Saad Goblan; Alyami, Abdullah Allas Hussain; Darahem, Raed Mohammed Ali Abu (Journal of Ecohumanism, 2024)
This paper provides an overview of the contribution of Health Information Technology (Health IT) to epidemiological research and public health: the Health IT Revolution in Epidemiology. From these findings, this paper critically assesses the role, opportunities, and difficulties that Health IT has made to epidemiological practices in the field. The analysis illustrates that Health IT has brought improvement in terms of precision and availability of epidemiological information, as well as new issues: for example, data security issues, ethical problems, and disparities in the availability of technologies. This paper discusses the plethora of current literature, methodologies, and actual applications to provide a comprehensive view of the impact of Health IT in epidemiology. The analysis discussion then stresses the challenge of meaningful and moral incorporation to capitalize on it in the global health environment.